Sosialisasi Gemar Makan Ikan Di Sekolah Dasar Negeri 015 Teratak Buluh Kabupaten Kampar - Sibagariang, Rina D'rita (Community Education Engagement Journal, 2020)
ABSTRACT Indonesia as a maritime country, has diversity of fish and abundant fish production. The level of fish consumption decreases with the amount of meat on the market. The reduced interest of students in consuming fish is a problem today. Gemarikan socialization aims to campaign, inform and invite students to eat fish and to know fish diversification, and is expected to be able to increase students interest in consuming fish. Participants in this activity were teachers and students of SD Negeri 015 Teratak Buluh, Siak Hulu District, Kampar Regency. The methods used are lectures, question and answer, games and eating nuggets together. It is hoped that students will like to eat fish and consume more fish than before and students will also be familiar with fish diversification products.